Dual-mode laser beam welding of similar and dissimilar material tab-to-busbar for electric vehicle battery pack - Nikhil Kumar; Venkat Vivek Pamarthi; Christopher Harris; Elliot Burbidge; Iain Masters (Journal of Advanced Joining Processes)
The escalation in electric vehicle (EV) adoption necessitates advanced laser joining techniques for critical battery pack components. However, using a standard Gaussian single-mode laser for joining similar and dissimilar material combinations e.g. aluminium/aluminium (Al/Al), aluminium/copper (Al/Cu) for tab-to-busbar connections often led to defects such as cracks and intermetallic compound (IMC) formation. This paper investigates using a dual-mode laser consisting of a core and ring to overcome these issues. In this research, 0.3 mm Al and Cu tabs were welded with 1.5 mm Al and Cu busbars using a 6 kW IPG dual-mode laser at a high welding speed of 1 m s-1. The study focussed on the effects of dual-mode parameters (i.e. core and ring beam power) and welding speed on tab-to-busbar connections, analysing the interplay between electrical contact resistance, temperature and IMC formation through electrical resistance tests, elemental and strength analysis. The results show, that using the ring beam along with the core beam reduces excessive melting and evaporation of Al and minimises the intermixing of Al and Cu solid solutions in the joint. In the Cu tab-to-Al busbar joint, increasing the ring beam intensity effectively reduces the convexity defect found with single-mode beam attributed to improved keyhole stability. Overall, in dual-mode laser welding, the ring beam protects the keyhole and reduces the IMC formation, while the core beam, with its high peak intensities, controls the penetration depth. This necessitates balancing both core and ring beam intensities for optimal weld quality. Further, the joint resistance for Cu tab-to-Cu busbar (51.90 μΩ) joint was the lowest followed by Cu tab-to-Al busbar (68.38 μΩ) joint, Al tab-to-Cu busbar (84.44 μΩ) joint and Al tab-to-Al busbar (114.12 μΩ) joint.